Armazenamento de sementes de soja em diferentes embalagens e atmosferas - Padia, Claudir Lari (2020)
The physiological quality of seeds has a direct influence on agricultural production; through the potential of vigorous plants production establishes a highly productive system with uniformity. Storage is one of the most important postharvest processes, especially in tropical regions such as Brazil; high temperatures negatively influence seed quality. Water content is one of the decisive factors in maintaining storage potential at safe levels, essential to prevent seed deterioration during storage. Seeds stored without moisture control in permeable packaging allow moisture exchange with the environment causing a hygroscopic imbalance of seeds during storage, causing further deterioration and reduced physiological quality. Today, there are several seeds of soybean cultivars available to the market, which adapt to different soils and climatic conditions, resulting in productivity gains, but qualitative results have not been identified in the postharvest aspects, especially in the storage stage. Thus, the objective of this study was to evaluate the seed quality of RR and RR2 PRO soybean cultivars stored in natural atmosphere with raffia packaging, in natural atmosphere with laminated packaging, modified atmosphere (-14 PSI) with polyethylene packaging, in refrigerated atmosphere (1 to 3 °C) with raffia packaging, refrigerated (1 to 3 °C) with laminated packaging, modified atmosphere (-14 PSI) and refrigerated (1 to 3 °C) with polyethylene packaging, over six months of storage. The experiment was characterized by a completely randomized design with three replications for each treatment, considering storage conditions, storage time and cultivars as sources of variation. Seeds were sampled from the different treatments every two months: at times zero, two, four and six months of storage for water content, bulk density, one thousand seeds weight, electrical conductivity and germination. The results were analyzed by the computer program Sisvar, version 4.0 to 5% probability, by the Tukey mean test. Subsequently, a polynomial regression analysis and a multivariate analysis of principal components and grouping with the aid of the R programming language were performed. In these analyzes, variables were standardized to prevent the measurement unit from affecting the results. For clustering, the average Euclidean distance and the helthmap clustering method were used. In the obtained results it was verified that the ambient temperature had amplitudes of 7.9 to 30.7 °C and the relative humidity of 33 to 95%, which may have influenced the storage of the stored soybean seeds through the increase or decrease. Gaseous exchange of atmospheric air and intergranular air due to vapor pressure differences, since the packages used are not impermeable. Under natural storage conditions, ambient and intergranular air temperatures ranged from 16.71 to 24.31 °C, while ambient and intergranular air relative humidity ranged from 74.30 to 84%. However, under refrigerated storage conditions the ambient and intergranular air temperature remained constant at 3 °C and the relative humidity at 60%. The vapor pressure ratios of the storage environments and intergranular air showed that the natural environment in raffia packaging (ANER) had the highest values (1.58 kPa), indicating that the intergranular vapor pressures were low in relation to the environment, in contrast to refrigerated environment in raffia packaging (ARER). (0.89 kPa), when the pressure ratios were lower, indicating that the intergranular air vapor pressure was high decreasing the difference from ambient vapor pressures. The seeds of cultivar RR remained with better physiological quality, while the seeds of cultivar RR2 remained with higher apparent specific mass during storage. The raffia and polyethylene packaging under the natural storage conditions, with refrigerated and modified atmosphere did not preserve the seed quality over the storage time. The storage conditions in natural atmosphere in laminated packaging (ANEL) and refrigerated atmosphere in laminated packaging (AREL) reduced the environmental effects of temperature and relative humidity, obtaining better results of physical and physiological seed quality. The storage time influenced the physical and physiological quality reduction of the seeds, except for AREL and ANEL that kept the qualities close to the initial conditions, during the six months of storage. It was concluded that the storage of soybean seeds in laminated packages with air valves presents sufficient gas and water vapor exchange between the seeds and the storage medium, eliminating the costly use of artificial refrigeration, which was equivalent in quality, according to the results obtained. Therefore, a new alternative for soybean seed storage is proposed, using air bag laminated big bags to minimize the qualitative losses of soybean seeds.